Pyrrolizidine alkaloids and health risk of three Boraginaceae used in TCM - Zan, Ke; Wang, Zhao; Hu, Xiao-Wen; Li, Yao-Lei; Wang, Ying; Jin, Hong-Yu; Zuo, Tian-Tian; Ma, Shuang-Cheng (Frontiers in Pharmacology, 2023)
The aim of this study was to develop an ultra-high performance liquid chromatography coupled with tandem mass spectrometry for the simultaneous quantification of eight pyrrolizidine alkaloids (PAs), namely intermedine, lycopsamine, intermedine N-oxide, lycopsamine N-oxide, 7-acetyllycopsamine, 7-acetyllycopsamine N-oxide, echimidine N-oxide, and echimidine in the three Boraginaceae used in TCM, involving Arnebia euchroma (AE), A. guttata (AG), and Lithospermum erythrorhizon (LE). The method was fully validated and successfully applied to determine the contents of these analytes in different species. The results indicated that the contents of these compounds in the three species were significantly different. Imermedine and imermedine N-oxide were common components in the eight tested PAs. 7-acetyllycopsamine and its N-oxide were not detected in AE; echimidine and its N-oxide were not detected in AG; lycopsamine and its N-oxide, 7-acetyllycopsamine and its N-oxide were not detected in LE. The total contents of 8 PAs in 11 batches of AG was341.56–519.51 μg/g; the content in 15 batches of LE was 71.16–515.73 μg/g, and the content in 11 batches of AE was 23.35–207.13 μg/g. Based on these results, the risk assessment was explored using the routine margin of exposure (MOE) combined with relative potency (REP) for oral and external usage, respectively. The findings of the risk assessment method of PAs based on MOE combined with the REP factor were consistent with the clinical toxicity results. As an oral herb, AE had low risk or no risk due to its low PA contents, and individual batches of LE were medium risk, while attention should be paid to their clinical use.AG was also low risk. The external use of the three Boraginaceae used in TCM was not associated with any risk. This study systematically explored the PA type and content of the three Boraginaceae used in TCM. Additionally, the refined risk assessment of PAs based on REP provided a more scientific basis for quality evaluation and rational use of the medicinal Boraginaceae used in TCM to improve public health.